Impact of Performance Appraisal System on Employees Motivation: Examining the Relationship between Payment System and Employee Satisfaction (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present study is focused to examine the relationship of employees payment and employees satisfaction. The study explains that the payment system is managed with a computerized system called payroll system. Employees are paid salary after adjusting for deductions and allowances. Mode of payment is bank. Attendance for complete month is calculated on 25 of every month with left days attendance is assumed. The problem in the existing system is the preparation of revised attendance due to assumed attendance. Employees payments have two main components- Direct and Indirect payments in the form of wages, salaries, incentives, commissions, and bonuses, and there are indirect payments in the form of financial benefits like employer-paid insurance and vacations.